UPAYA HUKUM PEMERINTAH ATAS PENYALAHGUNAAN TANAH GOVERNOR GROUND TERHADAP ALIH FUNGSI LAHAN - Malika Putri, Dita Karunia; Afiyah, Siti (LAW Specialist Jurnal Ilmiah Hukum, 2024)
Governor Ground land refers to land without ownership rights, which can be interpreted as abandoned land. Abandoned land is land controlled by the state where the legal relationship between the landowner and the land has been severed, as regulated in Article 27(a) of the Basic Agrarian Law (UUPA). The government’s authority over such land is stipulated in Article 2, paragraph (2) of the UUPA.This study aims to provide answers regarding the rights over Governor Ground land. The research employs normative legal methods, using a conceptual, case, and legislative approach. Legal materials were collected through literature review and analysis of articles and opinions from previous researchers. The findings indicate that Governor Ground land can be owned or utilized if specific requirements are met and permission is obtained from the government, particularly the National Land Agency (BPN).